Pola Kerja Wartawan Muda Dan Madya Di Era Digital - Anisa Setya Arifina; Prinisia Nurul Ikasari; Jaduk Gilang Pembayun (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This study examines the work patterns of middle and young journalists in the newspaper industry. Journalists work patterns seen from the process of selecting news, researching news, and writing news. With the advent of the digital era, these three processes can be seen by the consumption patterns of digital media for middle and young journalists. This study was conducted using a study case with in-depth interviews with journalists of the Suara Merdeka newspaper. The results showed that the presence of digital media is used by middle and young journalists in the local newspape for personal needs outside of journalistic duties. The reason for this is the pattern of digital media consumption of young and middle journalists who are included in the categories of “joiners” and “conversationalists”. In other words they are connoisseurs and spectators. For news development and idea searches, they rely more on news sources in the form of press releases, local government, e-mail and emergency services rather than internet research. This is related to the company's principles which try to minimize legal problems from published news.